Exploring the EQ-5D Dimension of Pain/Discomfort in Dermatology Outpatients from a Multicentre Study in 13 European Countries - Francesca Sampogna; Damiano Abeni; Uwe Gieler; Lucía Tomas Aragones; Lars Lien; Françoise Poot; Gregor B.E. Jemec; Csanád Szabó; Dennis Linder; Henriët van Middendorp; Jon Anders Halvorsen; Flora Balieva; et al. (Medical Journals Sweden, 2020)
Pain and discomfort are important symptoms in dermatology. The aim of this cross-sectional, multicentre study was to describe the prevalence of pain/discomfort and its associations in patients with several dermatological conditions across 13 European countries. The outcome was the prevalence of pain/discomfort according to a question of the EQ-5D questionnaire. Data collected from November 2011 to February 2013 were complete for 3,509 consecutive outpatients. Moderate or extreme pain/discomfort was reported by 55.5% of patients and 31.5% of controls with no skin conditions. The highest proportions were reported by patients with hidradenitis suppurativa (92.9%), leg ulcer (81.4%), prurigo (80%) and lichen planus (75.6%). Pain/discomfort was associated with older age, low educational level, clinical severity, flare on scalp or hands, itch, depression, anxiety, low quality of life, and thoughts of suicide. It is important to enquire specifically about pain/discomfort during clinical consultations and to address it when planning a patient's care.